Prevalence and risk factors predisposing low bone mineral density in patients with thalassemia - Ananvutisombat, Natnicha; Tantiworawit, Adisak; Punnachet, Teerachat; Hantrakun, Nonthakorn; Piriyakhuntorn, Pokpong; Rattanathammethee, Thanawat; Hantrakool, Sasinee; Chai-Adisaksopha, Chatree; Rattarittamrong, Ekarat; Norasetthada, Lalita; Fanhchaksai, Kanda; Charoenkwan, Pimlak (Frontiers in Endocrinology, 2024)
Background: A common complication of thalassemia is secondary osteoporosis. This study aimed to assess the prevalence and factors associated with low BMD in thalassemic patients.Method: This is a cross-sectional study. Eligible patients were males aged within 18-49 years or premenopausal women diagnosed with thalassemia in Chiang Mai University Hospital between July 2021 and July 2022. The diagnosis of low BMD by dual-energy x-ray absorptiometry (DXA) was defined as a Z-score of -2.0 SD or lower in either the lumbar spine or femoral neck. Clinical factors associated with low BMD were analyzed using a logistic regression model.Results: Prevalence of low BMD was 62.4% from 210 patients with a mean age of 29.7±7.6 years. The predominant clinical characteristics of low BMD thalassemia patients were being female, transfusion-dependent (TDT) and a history of splenectomy. From multivariable analysis, the independent variables associated with low BMD were transfusion dependency (odds ratio, OR 2.36; 95%CI 1.28 to 4.38; p=0.006) and body mass index (BMI) (OR 0.71; 95%CI 0.61 to 0.82; p<0.001).Among patients with low BMD, we observed a correlation between a Z-score with low IGF-1 levels (β=-0.42; 95% CI -0.83 to -0.01; p=0.040), serum phosphate levels (β=0.40; 95% CI 0.07 to 0.73; p=0.016) and hypogonadism (β=-0.48, 95% CI -0.91 to -0.04, p=0.031).This study found a prevalence of low BMD in 62.4% of subjects. Factors associated with low BMD were TDT and BMI. Within the low BMD subgroup, hypogonadism, serum phosphate and low serum IGF-1 levels were associated with a lower Z-score.